Hawking Radiation of Scalar and Vector Particles from 5D Myers-Perry Black Holes - Jusufi, Kimet; Övgün, Ali (Springer/Plenum Publishers, 2017)
In the present paper we explore the Hawking radiation as a quantum tunneling effect from a rotating 5 dimensional Myers-Perry black hole (5D-MPBH) with two independent angular momentum components. First, we investigate the Hawking temperature by considering the tunneling of massive scalar particles and spin-1 vector particles from the 5D-MPBH in the Painleve coordinates and then in the corotating frames. More specifically, we solve the Klein-Gordon and Proca equations by applying the WKB method and Hamilton-Jacobi equation in both cases. Finally, we recover the Hawking temperature and show that coordinates systems do not affect the Hawking temperature.
Keywords: 5-D Myers-Perry black hole; Qunatum tunneling; Klein-Gordon equation; Proca equation